Blockade by antiarrhythmic drugs of glibenclamide-sensitive K+ channels in Xenopus oocytes. - Sakuta, H. (1992)
1. The outward K+ current induced by KRN2391 (K+ channel opener) in Xenopus oocytes is blocked by glibenclamide. We have investigated the effects of various classes (I-IV) of antiarrhythmic drugs on this KRN2391-induced response. 2. All class I antiarrhythmic drugs (Na+ channel blockers) tested concentration-dependently suppressed KRN2391-induced responses with the rank order of potency (IC50 in microM), disopyramide (17.8) > aprindine (29.5) > propafenone (63.1) > ajmaline (145) > quinidine (151). Flecainide, SUN1165, lignocaine, mexiletine and procainamide were much less potent (IC50, 450- > 1000 microM) than quinidine. 3. The class II antiarrhythmic drugs (beta-blockers), timolol, (-)- and (+/-)- propranolol, and (+)- propranolol (a non-beta-blocker) inhibited KRN2391-induced K+ currents in a concentration-dependent manner with values for IC50 (microM) of 79, 131, 151 and 129, respectively, whilst butoxamine, oxprenolol, alprenolol, pindolol, nadolol, metoprolol and acebutolol were either weak (IC50, 300 microM-600 microM) or virtually inactive (IC50, > 1000 microM). 4. The class III antiarrhythmic drugs, amiodarone and (+)-sotalol scarcely affected KRN2391 responses. 5. All class IV drugs (Ca2+ antagonists) tested suppressed KRN2391-induced responses in a concentration-dependent manner with an IC50 of 6.3 microM for bepridil, 38 microM for prenylamine, 85 microM for verapamil and 135 microM for diltiazem. 6. In conclusion, antiarrhythmic drugs of classes I, II and IV potently blocked glibenclamide-sensitive K+ channels in Xenopus oocytes.